Translation and cultural adaptation of the Positive Aspects of Caregiving Scale for caregivers of people living with dementia in Brazilian context: a methodological study - Sofia Cristina Iost Pavarini; Aline Cristina Martins Gratão; Camila Rafael Ferreira Campos; Diana Quirino Monteiro; Elizabeth Joan Barham; Fabiana de Souza Orlandi; Gabriela Martins; Gustavo Carrijo Barbosa; Keila Cristianne Trindade da Cruz; Larissa Corrêa; Luana Aparecida da Rocha; Ludmyla Caroline de Souza Alves; et al. (São Paulo Medical Journal, 2024)
ABSTRACT BACKGROUND: The Positive Aspects of Caregiving (PAC) scale is used to assess psychosocial benefits provided to caregivers by the task of caring. The PAC scale consists of nine items, assessed using a five-point Likert scale, with higher values indicating greater positive perceptions and gains from the caregiving experience. OBJECTIVE: To translate and culturally adapt the PAC scale for informal Brazilian caregivers of people with dementia. DESIGN AND SETTING: A methodological study was conducted at the Federal University of São Carlos. METHODS: The following stages were carried out: Translation; Synthesis of the translations; Back-translation; Evaluation by an experts’ committee; and Pre-test. RESULTS: Two independent professionals translated the PAC scale. The consensus version was obtained by merging both translations, which were back-translated into English by a third translator. The expert committee comprised three specialists in the area and project researchers. All scale items presented a Content Validity Index of 1 (CVI = 1.0), and thus remained in the pre-final version of the instrument. The instrument was pre-tested with seven caregivers of people with dementia, the majority of whom were women (57.1%), with a degree of kinship corresponding to sons/daughters (57.1%) and an average age of 55.2 (± 4.1) years. The caregivers considered it clear and understandable and made no suggestions for changes. CONCLUSION: The PAC scale was translated and culturally adapted for use by informal caregivers of people with dementia in Brazil. However, a psychometric analysis of the instrument is necessary to provide normative data for this population group.